The link between sleep bruxism and oxidative stress based on a polysomnographic study - Michal Fulek; Weronika Frosztega; Mieszko Wieckiewicz; Anna Szymanska-Chabowska; Pawel Gac; Rafal Poreba; Grzegorz Mazur; Milena Sciskalska; Marta Kepinska; Adrian Martuszewski; Helena Martynowicz (Scientific Reports)
Abstract Oxidative stress is proven to increase cardiovascular risk and to diminish healthy life expectancy. Sleep bruxism (SB) is a prevalent masticatory muscle activity during sleep characterized by heterogeneous etiology and inadequately recognized pathophysiology. Recent theories have proposed a potential association between SB and oxidative stress. The aim of the research was to compare the antioxidant status between individuals with SB in contrast to those without SB. A total of 80 adults participated in a full-night polysomnography, assessed according to the American Academy of Sleep Medicine (AASM) standards. Blood samples were subsequently drawn via venipuncture for analysis. Participants were stratified into two groups based on their bruxism episode index (BEI). Using successive receiver operating characteristic (ROC) curves, optimal cut-off values were identified, enabling the detection of correlations with moderate (BEI > 2) and severe (BEI > 4) sleep bruxism. In the investigated group of patients we observed the relationship between bruxism and the examined parameters: total antioxidant status (TAS), advanced protein products (AOPP) and thiobarbituric acid-reacting substances (TBARS). Low TAS (≤ 0.14 mM and ≤ 0. 16 mM), high AOPP (≥ 82.44 µmol/l) and high TBARS (≥ 723.03 µmol/l and ≥ 1585.45 µmol/l) serum levels result in significantly higher sleep bruxism parameters. Sleep bruxism is related to oxidative stress markers. Elevated markers of lipid and protein peroxidation may be associated with endovascular damage and cardiovascular risk in sleep bruxers, but further research is needed in this topic.